2018
DOI: 10.5194/acp-18-7799-2018
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the enhanced effectiveness of NO<sub><i>x</i></sub> control from simultaneous reductions of VOC and NH<sub>3</sub> for reducing air pollution in the Beijing–Tianjin–Hebei region, China

Abstract: Abstract. As one common precursor for both PM2.5 and O3 pollution, NOx gains great attention because its controls can be beneficial for reducing both PM2.5 and O3. However, the effectiveness of NOx controls for reducing PM2.5 and O3 are largely influenced by the ambient levels of NH3 and VOC, exhibiting strong nonlinearities characterized as NH3-limited/NH3-poor and NOx-/VOC-limited conditions, respectively. Quantification of such nonlinearities is a prerequisite for making suitable policy decisions but limita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 31 publications
3
58
0
Order By: Relevance
“…The NH 3 concentration begins to increase in the morning (at approximately 08:00 LT) then reaches a plateau in the afternoon (8.5 to 15.5 ppb on average); the SO 2 concentrations show a similar diurnal variation to that of NH 3 . This type of diurnal variation for SO 2 was also found by Xu et al (2014); however, the cause of the common diurnal pattern between NH 3 and SO 2 during this field campaign requires further investigation. The NO * 2 concentration increases quickly in the afternoon and decreases in the evening.…”
Section: Feedback Between Hono Formation and Inorganic Secondary Aerosupporting
confidence: 71%
“…The NH 3 concentration begins to increase in the morning (at approximately 08:00 LT) then reaches a plateau in the afternoon (8.5 to 15.5 ppb on average); the SO 2 concentrations show a similar diurnal variation to that of NH 3 . This type of diurnal variation for SO 2 was also found by Xu et al (2014); however, the cause of the common diurnal pattern between NH 3 and SO 2 during this field campaign requires further investigation. The NO * 2 concentration increases quickly in the afternoon and decreases in the evening.…”
Section: Feedback Between Hono Formation and Inorganic Secondary Aerosupporting
confidence: 71%
“…The average overestimation of NO 2 was 22 % in Mexico City, which even increased to 50 % in the afternoon (Dunlea et al, 2007). Xu et al (2013) suggested that the chemiluminescence monitors overestimated NO 2 by less than 10 % in urban areas with fresh emission of NO x , but the positive bias went up to 30 %-50 % at the suburban sites. As described in Sect.…”
Section: Site Descriptionmentioning
confidence: 96%
“…NO 2 was calculated from the difference between NO and NO x . Studies indicated that NO 2 monitored with chemiluminescence was generally overestimated due to the conversion of the total odd nitrogen (NO y ) to NO by molybdenum oxide catalysts (McClenny et al, 2002;Dunlea et al, 2007;Xu et al, 2013). The positive bias was more significant in more aged air masses, resulting from higher levels of NO z (NO z =NO y − NO x ) (Dunlea et al, 2007).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Overall, the eastern US aerosol is predicted to be one of the most acidic locations, with average pH F near a value of 1 (Battaglia et al, 2017;Weber et al, 2016;Pye et al, 2018;Xu et al, 2015; and higher pH F , by about 1 unit, observed in locations of intensive agriculture with high NH 3 concentrations (Nah et al, 2018) and those influenced by larger particles . Higher aerosol pH (2-3 in pH F ) was estimated for Los Angeles in summer (Guo et al, 2017b), similar to observationally derived values for the eastern Mediterranean (0.5-2.8 pH F , Bougiatioti et al, 2016).…”
Section: Spatial and Temporal Variability Of Aerosol Phmentioning
confidence: 98%
“…The studies employing proxies likely suffered from problems with the proxies; themselves (as discussed above); and confounding factors such as correlations between organic aerosol and sulfate, a major source of acidity, that often occur in regional pollution Nguyen et al, 2015). These seemingly contradictory results were resolved once pH F was used, and the conclusions reached in these prior studies have been revisited based upon detailed understanding of the underlying chemical mechanisms and additional insight suggesting that the aerosol acidity is frequently not a limiting factor in catalyzing SOA formation Xu et al, 2015;Weber et al, 2016). Acid-catalyzed isoprene SOA has now been implemented in a wide variety of box model and chemical transport model applications that now rely exclusively on thermodynamic models for acidity estimates Marais et al, 2016;Riedel et al, 2016;Budisulistiorini et al, 2017).…”
Section: Proxies Based On Electroneutralitymentioning
confidence: 99%